2014
DOI: 10.1097/smj.0000000000000065
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Access to Health Services and Provider Information and Adverse Birth Outcomes: Findings from LaPRAMS, 2007–2008

Abstract: Findings support the need for a better understanding of discriminatory experiences and their impact on women's experiences during prenatal care and poor birth outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Four of the studies reviewed were qualitative designs, and 11 studies included quantitative designs . All of the qualitative studies were descriptive in nature.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four of the studies reviewed were qualitative designs, and 11 studies included quantitative designs . All of the qualitative studies were descriptive in nature.…”
Section: Resultsmentioning
confidence: 99%
“…In several of the studies, it was not clear what categories were provided to participants for self‐identification of race, and 3 of these studies included all African American participants . A study using Pregnancy Risk Assessment Monitoring System (PRAMS) data compared white women to black women without consideration of other racial groups given that white and black women comprise 95% of the population in the region examined . In one study, participants who identified as both African American and white were counted as African Americans in the analyses as the authors posited that participant experiences of racism were thought to better approximate those of African Americans versus whites .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations